A-211 Examination of the Personality Assessment Inventory and Performance Validity Tests: Correlation between Response Styles, Performance Effort, and Somatic Complaint. (28th August 2020) - C, Chan; J, Roth; J, Roberts; G, Getz
Abstract: Objective: Correlation between the performance validity measures from the Advanced Clinical Solution (ACS) package and select scales from the Personality Assessment Inventory (PAI) were examined to investigate relationships between performance effort and response styles involving negative impression (NIM), inconsistency (ICN), infrequency (INF), and somatic compliant (SOM) scales. Theoretical differences between symptom validity based on self-report questionnaires and credibility of performance on a performance validity tests (PVTs) were considered. Method: Archival data from clinical neuropsychological evaluations between the years 2015–2018 were reviewed, and 120 consecutive adult cases involving 68 males and 52 females between the ages of 19–69 were collected. Examined measures included: ACS—Word Choice Test (WCT), Reliable Digit Span, Visual Reproduction II Recognition, Logical Memory II Recognition, and the PAI. Spearman's rank-order correlation and point-biserial correlation analyses were conducted to examine the relationship between variables. Results: WCT had significant negative correlations with the NIM scale (rs(118) = −.203, p = .013). Modest correlations were found between SOM and WCT when examining PVT raw score (rs (118) = −.192, p = .018) and base rate performance (rs(118) = −.222, p = .007). Point-biserial serial analysis found a weak negative correlation between performance credibility and the SOM scale, which was statistically significant (rpb = −.221, n = 120, p = .008). Conclusions: NIM T-scores appear to be correlated with lower performance on the WCT, suggesting that an exaggerated or distorted impression of the self is associated with higher risk of poorer performance the stand-alone PVT. Correlation between embedded PVTs and PAI scales were inconsistent.